2017
DOI: 10.1016/j.chroma.2017.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Cold-induced aqueous acetonitrile phase separation: A salt-free way to begin quick, easy, cheap, effective, rugged, safe

Abstract: Cooling a 1:1 (v/v) solution of acetonitrile and water at −16° C is known to result in two clear phases. We will refer to this event as “cold-induced aqueous acetonitrile phase separation (CIPS)”. On a molar basis, acetonitrile is 71.7% and 13.6% in the upper and lower phases, respectively, in our study. The phase separation proceeds as a descending cloud of microdroplets. At the convenient temperature (typical freezer) employed here the lower phase is rather resistant to solidification, although it emerges fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 29 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…In other words, an ACN/water-based “in situ LLE” can be well realized through a simple cooling down process. In the past few years, this mechanism (naming as “cold-induced phase separation (CIPS),” “low-temperature-induced phase separation,” “homogeneous liquid-liquid microextraction,” “low-temperature partition,” and others) has been mainly utilized for drug/pesticide-residue analysis in food/environmental science ( 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ). However, its applicability for pretreatment of biotargets remains to be clarified.…”
mentioning
confidence: 99%
“…In other words, an ACN/water-based “in situ LLE” can be well realized through a simple cooling down process. In the past few years, this mechanism (naming as “cold-induced phase separation (CIPS),” “low-temperature-induced phase separation,” “homogeneous liquid-liquid microextraction,” “low-temperature partition,” and others) has been mainly utilized for drug/pesticide-residue analysis in food/environmental science ( 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ). However, its applicability for pretreatment of biotargets remains to be clarified.…”
mentioning
confidence: 99%
“…Starting from a 50% ACN‐water mixture, the upper phase contained 71.7% ACN on a molar basis and is therefore referred to as the ACN‐rich phase, while the lower water‐rich phase still contained about 13.6% ACN after phase separation. [ 24 ] Under the conditions after RP‐FPLC purification (40%–50% ACN, pH 1.9), the pigment migrated almost completely to the upper ACN‐rich phase. The cause of this migration could be ascribed to the molecular structure of the pigment, comprising of a complex mixture of several sorbicillinoid molecules having a highly oxygenated mono‐, bi‐ or tricyclic framework.…”
Section: Discussionmentioning
confidence: 99%
“…In literature it was found that solvent‐water systems using other organic solvents such as acetone, 2‐propanol or methanol do not undergo the same phase separation. [ 24 ] Therefore, to improve the pigment removal using CIPS, the pH value of the current ACN‐water mixture was altered from pH 2.0 –9.0. Higher pH values were avoided as HFBI is less stable at alkaline pH values.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of our reaction mixture, that is, the concentration of additive, is constant. Thus, only the volume ratio of ACN and water used for extraction or the extraction temperature [20][21][22] can be applied to affect the distribution of AETMA and IETMA into the water-rich and ACN-rich layer, as well as a volume of individual layers. The ACN/water volume ratio should be as high as possible to achieve a creation of two immiscible layers without any addition of other salts.…”
Section: No-additive Salting-out Liquid-liquid Extractionmentioning
confidence: 99%